NURSING CARE ON THE HOSPITAL WARD: AN INTEGRATIVE REVIEW - Fernanda Demutti Pimpão; Nalú da Costa Kerber; Fabiane Ferreira Francioni; Rosiane Filipin Rangel; Wilson Danilo Lunardi Filho (Universidade Federal do Paraná, 2012)
This integrative literature review aimed to identify how nursing care is undertaken on the hospital ward, and establish its relationship with the National Policy for Comprehensive Healthcare for Women. The search was carried out in the Latin-American and Caribbean System on Health Sciences Literature, the Nursing Database, International Literature in Health Sciences, and the Scientific Electronic Library Online, based on the descriptors hospital ward andnursing care, with 11 studies selected; there was no time cut-off in selecting the texts. There was a predominance of care permeated with prejudice, discrimination and de-humanization, in which the woman is not perceived as a subject with rights, counteracting the National Policy for Comprehensive Healthcare for Women. It is understood that the humanization of nursing care for women who have recently given birth remains a challenge for Nursing and for public health policies.